PENGARUH PENGAWASAN TERHADAP PRODUKTIVITAS KERJA PEGAWAI NEGERI SIPIL BAGIAN BIRO UMUM DI SEKRETARIAT DAERAH SULAWESI SELATAN - Salzabila, Andi Ghefira; Malik, Ihyani; Parawu, Hafiz Elfiansyah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
Supervision or controlling, namely an activity that aims to ensure that the implementation of an activity can run as planned. Supervision indicators are standard setting, assessment or evaluative, corrective action and work measurement. The aim of this research is to describe and explain the influence of supervision on the productivity of Civil Servants in the General Bureau at the South Sulawesi Regional Secretariat. This research is quantitative research using a survey method which aims to determine the effect of supervision on the work productivity of civil servants in the general bureau at the South Sulawesi regional secretariat. The research population was civil servants in the general bureau at the South Sulawesi governor's office, totaling 67 people with a sampling technique using random sampling. Data collection techniques use data prerequisite tests and simple linear regression. Based on the research results of the linearity test, the F value of the output obtained the calculated F value = 1.534 while the F table = 4.02. If F count F table, H0 with a value of 1.534 4.02 can be stated that there is a significant influence of supervision (X) on productivity (Y).